Nivel de calidad de la gestión de una institución educativa de la región Callao aplicando el modelo EFQM - Luque Cruz, Miguel (2010)
The research attempted to study the level of quality that has achieved the Polytechnic National of Callao school in Institutional Management. It was used simple descriptive method. In this research participated 5 principals, 50 teachers, 10 administrative and service people, 185 students and 50 family parents. The measurement instrument for the autoevaluation of the gestation of quality of the educative institution was the model EFQM adapted to Perú by Francisco Farro Custodio. The results showed that the level of quality that the school has achieved in Institutional Management is low.